Housing estate energy storage feasibility for a 2050 scenario - Sprake, David; Vagapov, Yuriy; Lupin, Sergey; Anuchin, Alecksey (2017 Internet Technologies and Applications (ITA), 2017)
The further penetration of renewable sources in the grid requires the implementation of energy storages in order to smooth out the variability and intermittent nature of renewables. This paper looks at the possibilities for a storage solution to meet an unprecedented situation of having no power input from renewables or an outage from grid sources for five consecutive days in the highest demand period of the year. The study uses as test case a 1000 house estate in the year 2050 with each property using electrical heating and electrical vehicle charging. The magnitude of power and energy estimated, together with the practicalities is then used to assess current storage solutions suitability and the likely possibilities of new innovations in the storage environment.